2017
DOI: 10.1016/j.micres.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of cefixime-induced gut microbiota changes by Lactobacillus cocktails and fructooligosaccharides in a mouse model

Abstract: Probiotics have been used to rebuild the antibiotic-induced dysfunction in gut microbiota, but whether the different strains of probiotics result in similar or reverse effects remains unclear. In this study, the different recovery effects of two cocktails (each contains four strains) of Lactobacillus and fructooligosaccharide against cefixime-induced change of gut microbiota were evaluated in C57BL/6J mice. The results show that the use of cefixime caused a reduction in the diversities of the microbial communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 60 publications
4
42
0
Order By: Relevance
“…This contention is supported by similar findings reported by Suez et al [7] during treatment of mice with a combination of ciprofloxacin and metronidazole concomitantly with an 11-strain probiotic including Lactobacillus and Bifidobacterium species. The dynamic alterations in Lactobacillales and Bifidobacteriales abundance during and after antibiotic treatment in the presence of a multi-strain synbiotic as found here is likely to have a bearing on other components of the microbiota, since members of the Lactobacillales and Bifidobacteriales order are known to modulate the activity and vitality of other gut microbes [52][53][54][55][56]. Specifically, soluble factors secreted from Lactobacillus are able to inhibit the growth of the human fecal microbiota in vitro by reducing the number of observed species and modulating the community structure [7].…”
Section: Discussionmentioning
confidence: 73%
“…This contention is supported by similar findings reported by Suez et al [7] during treatment of mice with a combination of ciprofloxacin and metronidazole concomitantly with an 11-strain probiotic including Lactobacillus and Bifidobacterium species. The dynamic alterations in Lactobacillales and Bifidobacteriales abundance during and after antibiotic treatment in the presence of a multi-strain synbiotic as found here is likely to have a bearing on other components of the microbiota, since members of the Lactobacillales and Bifidobacteriales order are known to modulate the activity and vitality of other gut microbes [52][53][54][55][56]. Specifically, soluble factors secreted from Lactobacillus are able to inhibit the growth of the human fecal microbiota in vitro by reducing the number of observed species and modulating the community structure [7].…”
Section: Discussionmentioning
confidence: 73%
“…Increasing evidence suggests that probiotics, which act as potential beneficial microorganisms, may help to prevent and treat the development of inflammatory diseases by regulating intestinal microbiota environment and host gut metabolism, in particular production of short‐chain fatty acids (SCFAs) . Shi et al reported that the protective effects of Lactobacillus cocktails on alleviating intestinal inflammation were related to restoring the cefixime‐induced gut microbiota and production of SCFAs in a murine model . Cremon et al studied 40 patients with irritable bowel syndrome (IBS) and observed that the risk of IBS could be reduced by Lactobacillus paracasei through modulating the gut microbiota structure and increasing the fecal acetate and butyrate levels .…”
Section: Introductionmentioning
confidence: 99%
“…1 Shi et al reported that the protective effects of Lactobacillus cocktails on alleviating intestinal inflammation were related to restoring the cefixime-induced gut microbiota and production of SCFAs in a murine model. 2 Cremon et al studied 40 patients with irritable bowel syndrome (IBS) and observed that the risk of IBS could be reduced by Lactobacillus paracasei through modulating the gut microbiota structure and increasing the fecal acetate and butyrate levels. 3 In addition, Simonyte Sjödin et al reported that probiotics regulating the gut microbiota-SCFA axis played a role in inducing the antiinflammatory response.…”
mentioning
confidence: 99%
“…Cefixime can reduce the diversity of the microbial community and lead to a significant decrease in the relative abundance of Firmicutes. The composition of gut microbiome of Lactobacillus and FOS probiotic mixture treatment group was much more diverse than that of the natural recovery group, indicating a better recovery effect of the probiotic cocktails on the gut microbiome (Shi et al, 2017). Moreover, the composition of the gut microbiome significantly changed in the HFD + fructose (HFF)-fed and the HFD + sucrose (HFS)-fed rats compared with the control diet (C)-fed rats; body-fat mass, metabolic inflexibility, glucose intolerance, lipopolysaccharide (LPS), insulin, renal reactive oxygen species (ROS), malondialdehyde (MDA), Nadphox, and Srebp-1 were significantly higher, and antioxidant enzymes and lean body masses were significantly lower in the HFS group with respect for the HFF group (Rosas-Villegas et al, 2017), indicating the harmful effect on the HFS group and the HFF group on gut microbiome as well as the health of humans.…”
Section: Close Relationships Among Diet Gut Microbiome and Health Carementioning
confidence: 95%